VISUAL IDENTITY DESIGN OF TANDATANYA COFFEE - Afriani, Farah; Wibawanto, Wandah (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2021)
Company identity is a description of a product or company which is used to compare other similar products or companies. The purpose of visual identity is to recognize and differentiate one another. In this final project, Tandatanya Coffee does not yet have an identity which describes the company itself. The steps used in designing Tandatanya Coffee's visual identity are pre-production, production and post-production. The writer chose simple with Japanese touch as the concept design according to its interior. Based on the analysis that has been done, the writer decided to make logo, stationary, packaging, apron, neon box, and promotional media.